A review of the effects of artificial light at night in urban areas on the ecosystem level and the remedial measures - Katabaro, Justine Mushobozi; Yan, Yonghong; Hu, Tao; Yu, Quan; Cheng, Xiang (Frontiers in Public Health, 2022)
The increased urban growth and high demand for improved human settlements have profoundly altered the way organisms experience the light-dark cycles. The typical natural dark parts of the earth are now bright at night at the expense of attaining improved urban settlements, nightscapes, extended human works, artistic expression, architectural aesthetics, and security enhancement. However, the acts to attain improved urban settlements have comparably posed a novel environmental pressure, and the damage to biodiversity has become a relentless threat to the ecosystem. Artificial light at night (ALAN) has pervasively increased over the past few decades and it is responsible for anthropogenic generated pollution. This type of pollution is considered among the leading stressors of biodiversity in urban areas. However, most research to date has focused on the effects of ALAN on individual species. Studies concerning the influence of ALAN on the ecosystem level are still very scarce, thus, leading to the limited understanding of the scope of potential effects of ALAN on ecosystems. This review work has examined and discussed the mechanism under which ALAN affects the ecosystem in urban territories. We firstly review the effect of ALAN on the physiology and behavior of individual organisms and species. Secondly, we triangulate these effects on the ecosystem level, focusing on community composition and population structure, consumer-resource interaction, primary productivity, food web, and trophic cascade. Finally, in admitting the importance of ALAN in human life, this paper gives insightful knowledge on how ALAN damage to the ecosystem could be limited, and the knowledge gaps that warrant further research.